Evaluasi Sistem Informasi Akuntansi Pendapatan dan Persediaan Pada PT. DEF - Kriswanto Kriswanto (Bina Nusantara University, 2012)
PT. DEF is a company engaged in the trading and distribution of food and frozen vegetables to customers in several restaurants and hotels in the big cities in Java. The problems faced by the company based on the results of observations made relating to revenue and inventory due to lack of internal controls in the company are because of the duplication of functions between the accounting and finance, many expired items should be disposed of and affect the company's earnings, collection of accounts receivable which resulted to financial turnaround interrupted, the data inventory is not accurate and complete so that the company's customer service to be less than satisfactory, and the problem of delay in making financial statements. The research method used in this study is data collection method which includes literature and field studies, analysis of findings, identifying the problems and the needs of information, and analysis method on object-oriented approach. The revenue accounting information systems and computerized inventory are expected to help the company run its operations, implement of internal controls within the company better, and overcome all the problems.